Transformasi Lahan Tidur Menjadi Lahan Produktif: Inisiasi Budidaya Sayuran Organik Skala Rumah Tangga di Desa Sulek Bondowoso - Nurfaizah, Selvi; Hidayah, Rohmatul; Safira Anastasya, Ihda; Satria Wira, Muhammad; Putra Susanto, Geraldi; Farhan Al Fikri, Awwalul (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This service aims to optimize idle land in the yards of residents of Sulek Village, Bondowoso Regency, through household-scale organic mustard cultivation. The activity was carried out in four stages, namely identification of unproductive land, preparation of facilities, planting and care of mustard greens, as well as mentoring and evaluation. A 350 m² demonstration plot was planted with organic mustard using a participatory approach. Seedlings were planted using environmentally friendly techniques and organic fertilization. The initial harvest reached 500 kg of good quality mustard, and of the 4.2 hectares of idle land identified, about 30% was successfully converted into productive land. The community response was very positive, demonstrated by the involvement of the hamlet head and community leaders in the socialization and development of household gardens. In addition to improving family food security, this activity strengthens the spirit of gotong royong, environmental awareness, and opens micro-economic opportunities for residents. This program demonstrates that organic backyard farming can be an effective strategy in building an independent, healthy and sustainable village.